2022
DOI: 10.1111/hel.12870
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii CNCM I‐745 supplementation modifies the fecal resistome during Helicobacter pylori eradication therapy

Abstract: Background:The gut microbiota is a significant reservoir of antimicrobial resistance genes (ARGs). The use and misuse of antimicrobials can select multi-resistant bacteria and modify the repertoire of ARGs in the gut. Developing effective interventions to manipulate the intestinal resistome would allow us to modify the antimicrobial resistance risk. Materials and Methods:Applying shotgun metagenomics, we compared the composition of fecal resistome from individuals treated with triple therapy for Helicobacter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
(114 reference statements)
0
0
0
2
Order By: Relevance
“…Discovered a century ago in 1920, S. boulardii has been shown to prevent and reduce the occurrence of diarrhea associated with antibiotic treatment (12)(13)(14). It also exerts protective properties in the treatment of Clostridioides difficile and Helicobacter infections (15)(16)(17). It has also been identified as protective in mouse models of IBD and IBS (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…Discovered a century ago in 1920, S. boulardii has been shown to prevent and reduce the occurrence of diarrhea associated with antibiotic treatment (12)(13)(14). It also exerts protective properties in the treatment of Clostridioides difficile and Helicobacter infections (15)(16)(17). It has also been identified as protective in mouse models of IBD and IBS (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…An interesting possibility for children is the hypothesis that administration of probiotics reduces H. pylori adhesion to gastric epithelial cells and prevents colonization. Further clinical trials are needed [91]. Probiotic co-supplementation to antibiotic therapies is reported in several studies in adults.…”
Section: Treatment Of H Pylori Infection In Agmentioning
confidence: 99%
“…Studies have also reported the long-term effects of antibiotics on gut microbiota, but individual differences and even intra individual differences are quite significant in the response to the same antibiotic 31 . In the triple therapy for H. pylori eradication, the addition of S. boulardii CNCM I-745 to the conventional antibiotic eradication therapy for H. pylori reduced the abundance of antimicrobial resistance genes, particularly those genes that confer resistance to lincosamides, tetracyclines, MLS-B, and a few genes in the beta-lactams class 32 .…”
Section: Disscusionmentioning
confidence: 99%